2014
DOI: 10.1007/jhep08(2014)133
|View full text |Cite
|
Sign up to set email alerts
|

Can a millicharged dark matter particle emit an observable γ-ray line?

Abstract: If a γ-ray line is observed in the near future, it will be important to determine what kind of dark matter (DM) particle could be at its origin. We investigate the possibility that the γ-ray line would be induced by a slow DM particle decay associated to the fact that the DM particle would not be absolutely neutral. A "millicharge" for the DM particle can be induced in various ways, in particular from a kinetic mixing interaction or through the Stueckelberg mechanism. We show that such a scenario could lead in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 71 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…(1) Some potential models have been proposed which might account for this observational anomaly [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16], the possibility of decaying sterile neutrinos or axions receiving particular attention. Given the wide expectation that SUSY should play a leading role in physics beyond the Standard Model, it is interesting to explore possible SUSY explanations for this signal.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Some potential models have been proposed which might account for this observational anomaly [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16], the possibility of decaying sterile neutrinos or axions receiving particular attention. Given the wide expectation that SUSY should play a leading role in physics beyond the Standard Model, it is interesting to explore possible SUSY explanations for this signal.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing Eqs. (12) and (13) one can see that production of gravitinos is more effective and when mass density of gravitinos is sufficient to explain the dark matter the abundance of sgoldstino is quite small: they form a subdominant fraction of the dark matter. Fraction ǫ ≡ Ω P /Ω 3/2 of produced sgoldstino checks with what constraint (4) gives if…”
Section: Setupmentioning
confidence: 98%
“…Although the observation has significance only at (3σ − 4σ) level and its explanation in the framework of known physics is possible it would be very exciting if the source of this line is in new physics probably related to so far elusive dark matter. Various scenarios have been studied including sterile neutrinos [3,4,5], XDM model [6,7], axion-like particles [8,9,10,11,12], millicharged particles [13] and light inflaton [14]. Below we are interested in possible explanations of this phenomena in the framework of supersymmetric theories.…”
Section: Introductionmentioning
confidence: 99%
“…The recently observed 3.5 keV X-ray line signal in the spectrum of 73 galaxy clusters as reported by the XMM-Newton X-ray observatory [6,7] will provide a strong hint for nongravitational Dark Matter interaction if confirmed by others. A few attempts have been already taken in order to explain this excess of X-ray signal by (i) decaying dark matter or annihilating dark matter, [8][9][10][11][12][13][14][15][16][17][18][19][20], (ii) magnetic dipolar dark matter (via upscattering of dark matter into an excited states and subsequent decay of excited states into dark matter and an X-ray photon), [21][22][23][24][25][26][27], (iii) others . From the recent explored scenarios it is found that such a photon signal, if the claimed excess persists, can be explained by late decay and/or annihilation of multi-keV mass dark matter, or decay of a second lightest metastable particle to lightest stable particle with a keV mass splitting.…”
Section: Introductionmentioning
confidence: 99%